Information-theoretic investigation of impact of huggable communication medium on prefrontal brain activation*. (2nd October 2019) - Sumioka, Hidenobu; Keshmiri, Soheil; Ishiguro, Hiroshi
ABSTRACT: This paper examines the effect of mediated hugs that are achieved with a huggable communication medium on the brain activities of users during conversations. We measured their brain activities with functional near-infrared spectroscopy (NIRS) and evaluated them with two information theoretic measures: permutation entropy, an indicator of relaxation, and multiscale entropy, which captures complexity in brain activation at multiple time scales. We first verify the influence of lip movements on brain activities during conversation and then compare brain activities during tele-conversation through a huggable communication medium with a mobile phone. Our analysis of NIRS signals shows that mediated hugs decrease permutation entropy and increase multiscale entropy. These results suggest that touch interaction through a mediated hug induces a relaxed state in our brain but increases complex patterns of brain activation. GRAPHICAL ABSTRACT: